Topinambur – new possibilities for use in a supplementation diet - Aleksandra Szewczyk; Mirosław Zagaja; Jarosław Bryda; Urszula Kosikowska; Dagmara Stępień-Pyśniak; Stanisław Winiarczyk; Marta Andres-Mach (Annals of Agricultural and Environmental Medicine, 2019)
Jerusalem artichoke ( Helianthus tuberosus Linne ) is a tuberous perennial plant of the Asteraceae family, which originates from North America, and is also known as wild sunflower or topinambur (TPB). It is characterized by good tolerance to frost, drought and poor soil, strong resistance to pests and plant diseases. For ages it was cultivated due to being both an edible tuber and having healing properties. In folk medicine, TPB leaves are used for the treatment of bone fractures and pain. TPB tubers are rich in sugar and have therefore been used for the production of functional food ingredients, such as inulin. Moreover, TPB is one of the potential crops for bioenergy production, such as bioethanol, biobuthanol and biodiesel, and chemicals (lactic acid, butyric acid). A number of bioactive compounds from the above ground parts of this plant have been isolated which have demonstrating antifungal, antioxidant and anticancer activities. In recent years, a number of animal experiments have been carried out to assess the health properties of TPB. Obtained results show that TPB possess a wide spectrum of medical applications, e.g. reduction in the levels of plasma glucose, total cholesterol and triglyceride. Interestingly, TPB has been shown to be a valuable alternative source of prebiotic compounds. This review article presents recent scientific reports on the chemical and biological properties of TPB and its potential use as a prebiotic diet supplement.